Beren and Lúthien - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Houghton Mifflin Harcourt, 2017)
Beren was a mortal man, but Lúthien was an immortal elf. Her father, a great elvish lord, in deep opposition to Beren, imposed on him an impossible task that he must perform before he might wed Lúthien. To show something of the process whereby this legend of Middle-earth evolved over the years, [Christopher Tolkien] has told the story in his father's own words by giving, first, its original form, and then passages in prose and verse from later texts that illustrate the narrative as it changed. Presented together for the first time, they reveal aspects of the story, both in event and in narrative immediacy, that were afterwards lost.--